Determinants of Intrauterine Fetal Death among Unbooked Paturients at the University of Port Harcourt Teaching Hospital, Southern Nigeria - Terhemen Kasso; Justina Omoikhefe Alegbeleye; Israel Jeremiah (Archives of Current Research International, 2020)
Background: Intrauterine fetal death (IUFD) is one of the most important problem in reproductive health, especially in developing countries. Unbooked pregnant women are more likely to suffer IUFD. Objectives: To determine the prevalence and risk factors of intrauterine fetal death among unbooked paturients at the University of Port Harcourt Teaching Hospital. Materials and Methods: A retrospective study of 344 unbooked women with intrauterine fetal death who presented at the labour ward of the University of Port Harcourt Teaching Hospital between January 1, 2011 and December 31, 2015. Data was obtained from their case / theater records and ward registers, encoded into a spreadsheet and analyzed using SPSS 22.0. Results were presented as means, rates and proportions. Associations between variables were assessed using students t-test and Pearson’s correlation. Differences were considered statistically significant at P < 0.05. Results: There were 12,421 deliveries during the study period: 10,136 (81.6%) received antenatal care while 2,285 (18.4%) did not. There was a total of 1,313 perinatal deaths, giving a perinatal mortality rate of 60.9/1000 births in unbooked patients and 18.4/1000 births in booked patients (P <0.01). Majority 149 (43.3%) of the IUFD occurred below 37 weeks and 123 (35.8%) at term. IUFD occurred prior to presentation in 320 (93%), of which most were referred from traditional birth attendants and religious institutions. Hypertensive disorders, abruptio placentae, obstructed labour, prolonged pregnancy, and prolonged rupture of membranes were the most common complications associated with IUFD. Conclusion: Pregnant women should be encouraged to register for antenatal care and deliver in health facilities with skilled attendants.